The Prominence of Weak Economies: Factors and Trends in Global News Coverage of Economic Crisis, 2009–2012 - Blondheim, Menahem; Segev, Elad; Cabrera-González, María de los Ángeles (International Journal of Communication, 2015)
This study investigates what makes a country newsworthy in economic news around the world. Employing Web-mining techniques on 35 leading news sites in the 10 most popular Internet languages, we calculated and tracked the relative prominence of countries in the world’s economic news from 2009 to 2012, a time of economic recession. Our findings suggest that major changes in GDP, even in relatively small economies, are no less important than overall GDP in explaining countries’ prominence in world economic news. Time-lag analysis of change in GDP and in news prominence identified three types of relation between news prominence and economic performance, reflecting the extent of world interest, press freedom, and the availability of reporting facilities. Network analysis of country co-mentions revealed three ripples when crisis hit noncore European countries, extending first to Europe’s leading economies, then global leading economies, and finally global developing economies. We discuss our findings’ implications for future research in the field.
Keywords: Crisis económicas - 2008-....; Información internacional; Economía; Globalización (Economía); Web mining; Economic news; News-flow theory; Globalization; Economic crisis; Media effects